Inhibition of Aluminium Corrosion in Hydrochloric Acid Using Nizoral and the Effect of Iodide Ion Addition. Issue 3 (2010) - Obot, I. B.; Obi-Egbedi, N. O.
Abstract : The effect of nizoral (NZR) on the corrosion inhibition of aluminium alloy AA 1060 in 2 M HCl solution was investigated using the mylius thermometric technique. Results of the study revealed that nizoral acts as corrosion inhibitor for aluminium in the acidic medium. In general, at constant acid concentration, the inhibition efficiency increases with increase in the inhibitor concentration. The addition of KI to the inhibitor enhanced the inhibition efficiency to a considerable extent. The adsorption of nizoral onto the aluminium surface was found to obey the Fruendlich adsorption isotherm. The value of the free energy for the adsorption process shows that the process is spontaneous.